The Ichthyophthirius disease in eel and the methods of the treatment - Vismanis, K.O.; Volkova, L.V.; Tarkach, G.M. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1971)
The pathogenic organism (Ichthyophthirius multifiliis Fouguet, 1876) is widely distributed among freshwater fish. It was established that the disease was one of the most dangerous eel Anguilla anguilla diseases in Latvia. The bath of 0.9 % solution of sodium chloride was recommended as the most effective remedy against the disease. Published Not Known